2018
DOI: 10.18203/2319-2003.ijbcp20185159
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of drug attitude, medication adherence and quality of life among psychiatric patients in South Indian population: a cross sectional study

Abstract: Background: In spite of many progresses in treatment of psychiatric disorders, medication nonadherence plays an important role in worsening of clinical condition and affects quality of life among psychiatric patients. There are numerous factors contributing for medication nonadherence among patients with mental illness. So, this study was conducted to assess psychiatric patients’ adherence of medication and to improve their quality of life with psychiatric disorder. The objectives of the study were to analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Low adherence was also linked to fear of medication adverse effects in the pharmacophobic group. In addition to helping patients with psychiatric illnesses live better lives, appropriate health education for pharmacophobia patients can increase medication adherence (Ganesan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Low adherence was also linked to fear of medication adverse effects in the pharmacophobic group. In addition to helping patients with psychiatric illnesses live better lives, appropriate health education for pharmacophobia patients can increase medication adherence (Ganesan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that patient's attitude towards treatment has an important role in treatment adherence. 9,10…”
Section: Attitudementioning
confidence: 99%
“…Previous studies have shown that patient's attitude towards treatment has an important role in treatment adherence. 9,10 Study shows that patients who have had adverse experiences with drugs taken during treatment have a more negative attitude towards treatment. 11…”
Section: Attitudementioning
confidence: 99%